PENINGKATAN ORGANIZATIONAL CITIZENSHIP BEHAVIOUR (OCB) GURU DENGAN CARA PENGUATAN KEPEMIMPINAN TRANSFORMASIONAL DAN EFIKASI DIRI - Naziroh Naziroh; Muhamad Entang; Sri Setyaningsih (JURNAL MANAJEMEN PENDIDIKAN, 2021)
IMPROVING TEACHERS' ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) BY STRENGTHENING TRANSFORMATIONAL LEADERSHIP AND SELF-EFFICIENCYThe success and sustainability of an organization is largely determined by the willingness of employees to behave well, not only when doing their main tasks, but also the extra behavior of wanting to be good employees. However, it is indicated that the teachers at MTs Negeri Jakarta Timur only carry out basic tasks and do not show behaviors that support organizational effectiveness beyond that. The purpose of this study was to determine the relationship between Transformational Leadership and Self-Efficacy on Organizational Citizenship Behavior either partially or jointly. The population in this study were MTSn teachers in the East Jakarta area with a sample of 243 respondents consisting of 18 MTSn in East Jakarta. Data was collected by distributing questionnaires and data processing was done by simple regression analysis and multiple regression analysis. The results showed that (1) Transformational Leadership has a positive and significant relationship with the teacher's Organizational Citizenship Behavior. (2) Self-efficacy has a positive relationship with the teacher's Organizational Citizenship Behavior. (3) Transformational Leadership and Self-Efficacy together have a positive and significant relationship with the teacher's Organizational Citizenship Behavior.